Analisis Dan Pembenahan Sistem Kompensasi Berdasarkan Metode Overlapping Dan Adhered Pada UKM XYZ - Kadek Dwi Trisna Larasati; Meilani Sulistina; Sevanya Sagala; Olyvia Yosephine Margareth Sitorus; Lindawati Kartika (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Compensation system is an approach to increase employees welfare in order to enhance their motivation resulting in increased productivity. Compensation includes all forms of reward, both financial and non-financial, in regards to services given by employees provided to the company. The object of this research is SME XYZ which operates in the food and beverage sector in East Jakarta. SME XYZ’s focus is selling Japanese food, such as sushi and ramen. Founded in 2013, SME XYZ has never made compensation adjustments to the business situation. Therefore, it is necessary to adjust the compensation given to employees based on applicable compensation principles as well as 3P Principles. The aim of this research is to determine the condition of the compensation system implemented by SME XYZ and to analyze the compensation system using adhered and overlapping methods. The results of this research indicate that SME XYZ does not have an ideal compensation system yet, so compensation adjustments are required. Adjustments are made using the adhered and overlapping method by grouping job titles into six grades. SME XYZ is advised to use the overlapping method in implementing the compensation system because it provides more comprehensive results.